1995
DOI: 10.1089/mdr.1995.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Resistant and Multidrug-Resistant Streptococcus pneumoniae in a Pediatrie Hospital in Zagreb, Croatia

Abstract: Sixty-four penicillin-resistant Streptococcus pneumoniae isolates [benzylpenicillin minimal inhibitory concentrations (MICs) between 0.05 and 1.6 micrograms/ml] recovered at the Pediatric Hospital "Dr. Fran Mihaljevic" in Zagreb, Croatia between October 1990 and March 1993 were analyzed for serotype, antibiotic susceptibility patterns, and chromosomal relatedness using pulsed-field gel electrophoretic (PFGE) analysis of chromosomal DNA fragmented by digestion with the SmaI endonuclease. Hospital "Dr. Fran Miha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, because PFGE patterns were not available in that publication, the genetic similarity between the strains could not be verified. No resemblance with the ROM-1 and ROM-12 clones described here was found when we compared them with other unique penicillin-resistant clones of pneumococci, such as the predominantly 19A clone identified in Hungary [25] (A.T., unpublished data), the serotype 14 and 19A clones in the Czech Republic and Slovakia [26], the 2 internationally spread clones with serotypes 23F and 9 or 14 detected in many countries, including Croatia [27] and Bulgaria [28], and the several other Bulgarian clones [28].…”
Section: Discussionmentioning
confidence: 63%
“…However, because PFGE patterns were not available in that publication, the genetic similarity between the strains could not be verified. No resemblance with the ROM-1 and ROM-12 clones described here was found when we compared them with other unique penicillin-resistant clones of pneumococci, such as the predominantly 19A clone identified in Hungary [25] (A.T., unpublished data), the serotype 14 and 19A clones in the Czech Republic and Slovakia [26], the 2 internationally spread clones with serotypes 23F and 9 or 14 detected in many countries, including Croatia [27] and Bulgaria [28], and the several other Bulgarian clones [28].…”
Section: Discussionmentioning
confidence: 63%
“…This phenomenon has been particularly highlighted by the worldwide spread of the serotype 23F pneumococcal clone (Spain 23F -1), first identified in Spain in the early 1980s (37) and resistant to penicillin, chloramphenicol, and tetracycline (and sometimes erythromycin). This successful clone has now been found in the United States (26, 37), South Africa (23), the United Kingdom (7), South America (5, 6, 12, 43), several other countries in Europe (29,30,42,46,48,50,58,61), and the Far East (34,47,59). Serotype 19F (7), 14 (4), 19A (9), 9N (40), and 3 (40) and serogroup 6 (54) variants of this clone have also been reported in various regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Clonally related S. pneumoniae strains implicated in the geographic spread of penicillin have generally been found to be highly resistant [39][40][41]. Studies from several countries have shown that S. pneumoniae strains with intermediate-level resistance to penicillin demonstrate large variations in their genetic background [42][43][44]. However, in Brazil, analysis of strains from reference laboratory collections by pulsed-field gel electrophoresis has identified clusters of isolates with intermediatelevel resistance, including those belonging to serotype 14, that were obtained from geographically distinct regions [45].…”
Section: Discussionmentioning
confidence: 99%